Qingda Granule Attenuates Angiotensin II-Induced Renal Apoptosis and Activation of the p53 Pathway - Linzi Long; Linzi Long; Linzi Long; Xiuli Zhang; Xiuli Zhang; Ying Wen; Ying Wen; Jiapeng Li; Lihui Wei; Lihui Wei; Lihui Wei; Ying Cheng; et al. (Frontiers Media S.A., 2022)
Background: Qingda granules (QDG) exhibit antihypertension and multiple-target-organ protection. However, the therapeutic potential of QDG on hypertensive renal injury remains unknown. Therefore, the main objective of the current study is to explore the effects and underlying mechanisms of QDG treatment on renal injury in angiotensin (Ang) II-infused mice.Methods and results: Mice were infused with Ang II (500 ng/kg/min) or saline for 4 weeks with subcutaneously implanted osmotic pumps. After infusion, mice in the Ang II + QDG group were intragastrically administrated with QDG daily (1.145 g/kg/day), whereas the control group and Ang II group were intragastrically administrated with the same amount of double-distilled water. Blood pressure of the mice monitored using the CODA™ noninvasive blood pressure system revealed that QDG treatment significantly attenuated elevated blood pressure. Moreover, hematoxylin-eosin staining indicated that QDG treatment ameliorated Ang II-induced renal morphological changes, including glomerular sclerosis and atrophy, epithelial cell atrophy, and tubular dilatation. RNA-sequencing (RNA-seq) identified 662 differentially expressed transcripts (DETs) in renal tissues of Ang II-infused mice, which were reversed after QDG treatment. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis based on DETs in both comparisons of Ang II vs. Control and Ang II + QDG vs. Ang II identified multiple enriched pathways, including apoptosis and p53 pathways. Consistently, terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) staining and Annexin V staining revealed that QDG treatment significantly attenuated Ang II-induced cell apoptosis in renal tissues and cultured renal tubular epithelial cell lines (NRK-52E). Furthermore, western blot analysis indicated that Ang II infusion significantly upregulated the protein expression of p53, BCL2-associated X (BAX), cle-caspase-9, and cle-caspase-3, while downregulating the protein expression of BCL-2 in renal tissues, which were attenuated after QDG treatment.Conclusion: Collectively, QDG treatment significantly attenuated hypertensive renal injury, partially by attenuating renal apoptosis and suppressing p53 pathways, which might be the underlying mechanisms.